Markedly different patterns of imbibition in seeds of 48 Acacia species. Issue 4 (16th December 2019) - Burrows, Geoffrey E.; Alden, Rowan; Robinson, Wayne A.
Abstract: The seeds of most Australian acacias have pronounced physical dormancy (PY). While fire and hot water (HW) treatments cause the lens to 'pop' almost instantaneously, for many Acacia species the increase in germination percentage can be gradual. If PY is broken instantly by HW treatment, why is germination often an extended process? Control and HW treatments were performed on seeds of 48 species of Acacia . Seeds were placed on a moist substrate and imbibition was assessed by frequently weighing individual seeds. In the two soft-seeded species all control seeds were fully imbibed within 6–24 h, while in hard-seeded species very few control seeds imbibed over several weeks. In 10 species over 50% of the HW-treated seeds imbibed within 30 h, but mostly the percentage of imbibed seeds gradually increased over several weeks. Some seeds in a replicate would imbibe early, while others would remain unimbibed for many days or weeks then, remarkably, become fully imbibed in less than 24 h. While HW treatment broke PY almost instantaneously, it appeared that in many Acacia species some other part of the testa slowed water from reaching the embryo. This process of having staggered imbibition may be a way of ensuring not all seeds in a population germinate after small rain events. Thus it appears the lens acts as a 'fire gauge' while some other part of the seed coat acts as a 'rain gauge'.